Click Chemistry in Natural Product Modification - Zhang, Xiang; Zhang, Shuning; Zhao, Songfeng; Wang, Xuan; Liu, Bo; Xu, Hongtao (Frontiers in Chemistry, 2021)
Click chemistry is perhaps the most powerful synthetic toolbox that can efficiently access the molecular diversity and unique functions of complex natural products up to now. It enables the ready synthesis of diverse sets of natural product derivatives either for the optimization of their drawbacks or for the construction of natural product-like drug screening libraries. This paper showcases the state-of-the-art development of click chemistry in natural product modification and summarizes the pharmacological activities of the active derivatives as well as the mechanism of action. The aim of this paper is to gain a deep understanding of the fruitful achievements and to provide perspectives, trends, and directions regarding further research in natural product medicinal chemistry.